Determining the most suitable frequency and shaking time for olive harvesting by a pneumatic branch shaker - A Rezaei (Ferdowsi University of Mashhad, 2016)
Introduction Olive (Oleo europaea) includes about 20 species of small trees from Oleaceae family. This point should be considered that Iran has allocated only a small universal market to its olive products in spite of having high production potentials; so that about 23 provinces of this country can produce olive products. Therefore mechanizing of olive production and encouraging to develop olive trade are among the effective methods for development of this market. On the basis of IOOC report, the production of olive oil in 2008-2009 in Iran and all over the world has been 3 and 2866.5 thousand tons, respectively. Currently, harvesting olive product is done by hand in Iran. The expensiveness of work force and providing the needed workers are considered as the biggest problem in olive harvesting. While harvesting the tall trees, the workers use beating method by wood sticks which causes the fruits to be damaged and their quality to be decreased. The harvesting method which the quality and quantity of the olive final products is under its effect and also high expenses of harvesting by hand are considered as the two important factors in developing the mechanical harvesting of olive. For this purpose, the mechanized harvesting of olive should be considered for producing olive conserve and olive oil and decreasing expenses of harvesting. Considering the conducted studies on one hand and shortage of informational resources in the country on the other hand, a research was designed and performed with the following purposes: Designing and fabricating of a portable pneumatic branch shaking system. Determining the best frequency and oscillation duration for harvesting olive by the constructed system. Materials and Methods The branch shaking system is made of two general parts: (a) The set of branch shaker driving unit. (b) The portable vibration arm. For constructing the set of vibrating arm, two experiments “elasticity and inflectionˮ of tree branches were conducted and the maximum force of 362.40 N was registered and it was considered as the base of computations. Then a double-action pneumatic jack with the internal diameter of 32 mm and the rod diameter of 12mm with the stroke length of 200 mm was selected. An electronic circuit was designed and developed for ordering the solenoid valve to control the flow. The system was transferred to one of the olive garden’s located in kilometer 5 of Sarvestan – Fasa road in Fars province in order to be evaluated. The effects of three oscillation frequencies of 12, 16 and 20 Hz and three oscillation durations of 5, 10 and 15 seconds at constant amplitude of 5 cm on detachment percentage of olive fruit was investigated through a factorial 3×3 experiment based on completely randomized design with four replications. Then the most suitable frequency and vibration duration was selected for harvesting olive by this system. For measuring the static detachment force of the fruits, a tensile force dynamometer system model FG-5100 made by Lutron Company was used with the accuracy of 0.1 N and a maximum capacity of 980 N. Results and Discussion The variance analysis of the investigated features on the basis of the factorial experiment based on completely randomized designs was conducted through using SPSS software. The results showed that both frequency of vibration and oscillation duration had significant effect on the shaker performance; with no significant interaction effects which implies the independence of the debated variables. Comparing the means by using Duncan test at 1% significance level for features of oscillation frequency and duration of shaking showed that at any constant duration of oscillation, increasing of oscillation frequency significantly increases the percentage of the olive fruit detachment. This increase is due to the increase of dynamic force with the second power of oscillation frequency compared to the static separating force (Murphy, 1950). It was observed that the calculated dynamic force is larger than the static force for separating the fruit in frequencies of 16 and 20 Hz, but since the dynamic force is variable at each point of the branch, 84.50 percent of fruits are separated from branches at frequency of 16 Hz and 87.25 percent of the fruits are separated from branches at frequency of 20 Hz. Conclusions At the end, the frequency of 20 Hz with 5 second duration of oscillation was selected as the most suitable treatment for this branch– shaker in harvesting oil-type olives.